2023
DOI: 10.3389/fped.2023.1135319
|View full text |Cite
|
Sign up to set email alerts
|

Impact of guidelines implementation on empiric antibiotic treatment for pediatric uncomplicated osteomyelitis and septic arthritis over a ten-year period: Results of the ELECTRIC study (ostEomyeLitis and sEptiC arThritis tReatment in children)

Abstract: BackgroundDue to the growing evidence of the efficacy of intravenous (IV) cefazolin with an early switch to oral cefalexin in uncomplicated pediatric osteomyelitis (OM) and septic arthritis (SA) in children, we changed our guidelines for empiric antibiotic therapy in these conditions. This study aims at evaluating the impact of the guidelines' implementation in reducing broad-spectrum antibiotic prescriptions, duration of IV antibiotic treatment and hospital stay, treatment failure and recurrence.Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Of note, studies that report hospitalization cost based on administrative data sets are considered at risk of selection bias because of inaccurate classification of diseases in hospital coding systems. Loss of follow-up and missing data were common issues, and only 9 studies explicitly mention guideline adherence 30,31,36,37,39,40,42,44,51 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, studies that report hospitalization cost based on administrative data sets are considered at risk of selection bias because of inaccurate classification of diseases in hospital coding systems. Loss of follow-up and missing data were common issues, and only 9 studies explicitly mention guideline adherence 30,31,36,37,39,40,42,44,51 .…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen publications were identified that met criteria by introducing a clinical care innovation and reporting its impact on LOS 12,13,[29][30][31][32][33][34][35][36][37][38][39][40][41][42] (Table III). Studies that only explored the efficacy of shorter antibiotic treatment have not been included as this is previously established information.…”
Section: Clinical Care Innovations To Streamline Inpatient Care and R...mentioning
confidence: 99%
See 1 more Smart Citation
“…La incidencia se estima en 1.2 a 13 casos por 100,000 niños por año. 2 Staphylococcus aureus (S. aureus) es el principal agente etiológico en 60 a 75% de las OM. Con una recurrencia y persistencia de la infección en 40% de los casos.…”
Section: Revisión De La Literaturaunclassified
“…Siempre se debe obtener un hemocultivo en el caso de osteomielitis aguda antes de iniciar el tratamiento antibiótico, a pesar de las bajas tasas de positividad (10-40%). 2 Aunque las alteraciones óseas radiológicas se presentan después de siete días de evolución, la radiografía simple es un método útil de primera línea para evaluar la infección ósea donde no se cuenta con otros estudios de imagen. Las alteraciones radiográficas son detectadas en 35% de los casos y la alteración más frecuente es la reacción perióstica.…”
Section: Continuación Del Caso Clínicounclassified